Competencias específicas del ingeniero de sistemas de la Universidad de la Costa CUC, frente a las pruebas Saber Pro (2015)
In this research project "The specific skills and knowledge test pro engineer CUC systems". This research was aimed to analyze the specific competencies Systems Engineer to identify the degree of mastery of the students at the University of Costa, opposite Saber Test Pro. As central theoretical references to Eliseo Verón. (1969 and 1970) which proposes the concept of ideological competition, defined as the set of specific organizations to make selections and a certain speech ways, in this regard the working world today requires an education for work, where he cognitive and psychological imperatives are to humans. On the other hand the same project Tunnig, proposes teaching competence and seeks an integrated system for uniform education, for extending and facilitating global academic mobility, Tunnig for Latin America considers the skills and the knowledge, skills both specific and transverse these requirements to be met by a graduate to meet the demands of the context in which it is immersed. Whereas the skills to be developed gradually and reach some hobble an evaluation process at different stages. It is also based on the issues raised by ICFES: as soon finds that the evidence KNOW PRO, is an instrument part with other processes and actions that lead to assess the quality of public education services and exercise their inspection and surveillance. These serve a process of evaluation of generic and specific skills. The methodology in which the research is framed is the positivist paradigm. Derived from the advances of natural science and the use of the experimental method, in which the late nineteenth century, was established as a model of scientific research. The methodology used resulted throw teachers 27.3% agree, regarding the knowledge of the specific skills assessed students of Systems Engineering Program in testing pro know.